Clinical and genetic characteristics in patients under 30 years with sporadic pituitary adenomas. Issue 4 (27th August 2021) - Martínez de LaPiscina, Idoia; Portillo Najera, Nancy; Rica, Itxaso; Gaztambide, Sonia; Webb, Susan M; Santos, Alicia; Moure, Maria Dolores; Paja Fano, Miguel; Hernandez, Maria Isabel; Chueca-Guindelain, Maria Jesús; Hernández-Ramírez, Laura Cristina; Soto, Alfonso; et al.
Abstract: Objective: Pituitary adenomas (PA) are rare in young patients, and additional studies are needed to fully understand their pathogenesis in this population. We describe the clinical and genetic characteristics of apparently sporadic PA in a cohort of young patients. Design: Clinical and molecular analysis of 235 patients (age ≤ 30 years) with PA. Clinicians from several Spanish and Chilean hospitals provided data. Methods: Genetic screening was performed via next-generation sequencing and comparative genomic hybridization array. Clinical variables were compared among paediatric, adolescent (<19 years) and young adults' (≥19–30 years) cohorts and types of adenomas. Phenotype–genotype associations were examined. Results: Among the total cohort, mean age was 17.3 years. Local mass effect symptoms were present in 22.0%, and prolactinomas were the most frequent (44.7%). Disease-causing germline variants were identified in 22 individuals (9.3%), more exactly in 13.1 and 4.7% of the populations aged between 0–19 and 19–30 years, respectively; genetically positive patients were younger at diagnosis and had larger tumour size. Healthy family carriers were also identified. Conclusions: Variants in genes associated with syndromic forms of PAs were detected in a large cohort of apparently sporadic pituitary tumours. We have identified novel variants in well-known genes and set the possibility of incomplete disease penetrance in carriers of MEN1 alterations or a limited clinical expression of the syndrome. Despite the low penetrance observed, screening of AIP and MEN1 variants in young patients and relatives is of clinical value.